How can male not be a teacher of pupils: Assessing stereotypes among teachers in primary school - Abayomi Israel Olaofe; Yusuf Olayinka Shogbesan; Babajide Gboyega Abidogun; Zozonaebi Frederick; Wahyun Bardianing Panggalih; Muhammad Kalle Istighfar; Mira Fatasya Aulia (EduStream: Jurnal Pendidikan Dasar, 2026)
Male teachers remain considerably under-represented in primary education globally due to incessant socio-cultural stereotypes in the system of educating young children. This study assessed stereotypes among teachers regarding male involvement in early-years education. Using a quantitative design, the Early Years Teachers' Stereotype Scale (EYETESS) was administered to n-122 educators and parents. Results revealed that primary school teaching continues to be perceived as a female-oriented profession (77.1% agreement), with men facing social stigma, masculinity doubts, and fear of false accusations (85.3% agreement). Parental attitudes were ambivalent, while expressing general trust in male teachers, parents showed reluctance regarding actual care arrangements. Male educators experience social isolation as gender minorities, inadequate professional support, gendered role expectations (channelling men into physical/disciplinary roles), and barriers to career advancement. The study concludes that institutional prejudices, stereotypes, and the psychological burden of working in suspicion promote a cycle of discouragement debarring male teachers from entry and retention in the sector. The stereotype can be eliminated through social enlightenment campaigns, gender-balanced recruitment policy, and institutional support networks for male teachers.